Experimental evaluation of effectiveness of distribuned acoustic radiator in the system of radio acoustic sounding of the atmosphere - Kartashov, V.M.; Babkin, S.I.; Tolstoy, E.G. (Radiotekhnika, 2018)
An estimation of efficiency of the distributed acoustic radiator using in the RAS system , when measuring meteorological quantities, is carried out experimentally. A good coincidence of results of the wind speed measurement performed with the comparative means (RASS and mast anemorumbometer) for some averaging is shown, though the standard deviations of results of measurement carried out using the RAS system and the anemorumbometer are markedly different due to methodological and technical factors. In addition, the use of the distributed emitter in the RAS system gives a real possibility of simultaneous recording of air humidity in the investigated atmosphere layer and also improves the accuracy of recording temperature profiles by using the maximuma of the video pulses amplitude for calculations. The RAS system with the distributed acoustic radiator can be made in a mobile version for synchronous measurements of the main meteorological values: the speed and direction of the horizontal wind, temperature and humidity of air in the field.